Dark matter cores in massive high-z galaxies formed by baryonic clumps. Issue 1 (11th May 2022) - Ogiya, Go; Nagai, Daisuke
ABSTRACT: The rotation curves of some star-forming massive galaxies at redshift two decline over the radial range of a few times the effective radius, indicating a significant deficit of dark matter (DM) mass in the galaxy centre. The DM mass deficit is interpreted as the existence of a DM density core rather than the cuspy structure predicted by the standard cosmological model. A recent study proposed that a galaxy merger, in which the smaller satellite galaxy is significantly compacted by dissipative contraction of the galactic gas, can heat the centre of the host galaxy and help make a large DM core. By using an N -body simulation, we find that a large amount of DM mass is imported to the centre by the merging satellite, making this scenario an unlikely solution for the DM mass deficit. In this work, we consider giant baryonic clumps in high-redshift galaxies as alternative heating source for creating the baryon dominated galaxies with a DM core. Due to dynamical friction, the orbit of clumps decays in a few Gyr and the baryons condensate at the galactic centre. As a back-reaction, the halo centre is heated up and the density cusp is flattened out. The combination of the baryon condensation and core formation makes the galaxy baryon dominated in the central 2–5 kpc, comparable to the effective radius of the observed galaxies. Thus, the dynamical heating by giant baryonic clumps is a viable mechanism for explaining the observed dearth of DM in high redshift galaxies.